2020
DOI: 10.1093/cid/ciz1235
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Human Immunodeficiency Virus–Related Gut Microbiota Alterations on Metabolic Comorbid Conditions

Abstract: Background We aimed to identify a human immunodeficiency virus (HIV)–related microbiota signature, independent of sexual preferences and demographic confounders, in order to assess a possible impact of the microbiome on metabolic comorbid conditions. Methods Bacterial 16S ribosomal RNA analyses were performed on stool samples from 405 HIV-infected and 111 uninfected participants of the Copenhagen Comorbidity in HIV Infection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
54
2

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(57 citation statements)
references
References 34 publications
1
54
2
Order By: Relevance
“…A previous report from our group demonstrated a polymicrobic flora in the blood of HIV-infected subjects with inadequate immune recovery on cART (30), raising the question of whether blood microbiota merely reflects the microbial composition in the gut or actively contributes to HIV pathogenesis. In keeping with this observation, recent studies have demonstrated a role of blood microbiota in the onset of diabetes and athero-thrombotic disease in the general population (31,32), possibly confirming a role of blood dysbiosis in non-AIDS related co-morbidities (33).…”
Section: Introductionsupporting
confidence: 65%
“…A previous report from our group demonstrated a polymicrobic flora in the blood of HIV-infected subjects with inadequate immune recovery on cART (30), raising the question of whether blood microbiota merely reflects the microbial composition in the gut or actively contributes to HIV pathogenesis. In keeping with this observation, recent studies have demonstrated a role of blood microbiota in the onset of diabetes and athero-thrombotic disease in the general population (31,32), possibly confirming a role of blood dysbiosis in non-AIDS related co-morbidities (33).…”
Section: Introductionsupporting
confidence: 65%
“…Moreover, gut microbiota–derived metabolites such as short-chain fatty acids (SCFAs) have been shown to protect the gut epithelial barrier and reduce inflammation levels in PWH receiving ART [ 36–38 ]. Composition of the gut microbiota has been associated with disease outcome in ART-treated PWH [ 26 , 31 , 33 , 39 , 40 ].…”
mentioning
confidence: 99%
“…Although prior studies have connected LBP-associated inflammation with worse metabolic health (27, 28, 63); the strength of this relationship is disease specific with less clear results in obesity-associated metabolic disease (29, 30). An importance of bacterial translocation in HIV-associated metabolic syndrome was demonstrated in a recent study of metabolic comorbidities in HIV-positive individuals which found that lower CD4 nadir and/or AIDS events, HIV-associated microbiota, and low alpha diversity was correlated with increases in sCD14 and LBP and increase risk of metabolic syndrome (31). Additionally, in our study LBP was correlated with age and BMI, a relationship that was previously observed in a cohort of HIV-negative men of African ancestry with this trio being further associated with adiposity and pre-diabetes (64).…”
Section: Discussionmentioning
confidence: 99%
“…hemodialysis patients) has been described (27), however there are mixed data regarding a role in obesity associated metabolic disease (28)(29)(30). Additionally, a recent study of metabolic syndrome in PLWH found greater immune dysfunction and a more HIV-associated microbiome associated with risk of metabolic syndrome (31).…”
mentioning
confidence: 99%